Efektivitas Metode Pengepakan Kering untuk Lobster Air Tawar (Cherax quadricarrinatus) dalam Kondisi Hidup - Much Noor Rifa’i (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2025)
Dry packing with the principle of hibernation aims to suppress the metabolic processes of an organism so that it can survive under minimal environmental conditions. This study aims to determine the effectiveness of the dry packing method on the survival of freshwater crayfish (Cherax quadricarrinatus) tested with dry packing for 15, 20, and 25 hours. Before packing, the crayfish were ensured to be healthy and free from deformities. The packing was carried out using styrofoam lined with cardboard and filled with dried banana leaves, with a density of 20 crayfish of 10 cm size per package. The results showed that packing with dried banana leaves for 25 hours resulted in a 100% survival rate after packing, and the crayfish were able to become active again after 3 days. The dry packing method using dried banana leaves was proven effective in maintaining the survival of freshwater crayfish under live conditions during long packing durations. This study contributes to the development of efficient packing techniques for transporting freshwater crayfish alive.